Bethany Aram y Bartolomé Yun-Casalilla (Eds.). Global Goods and the Spanish Empire, 1492-1824. Circulation, Resistance and Diversity. London, Palgrave Macmillan, 2014, X + 322 págs., ISBN: 978-1-137-32404-7. - Bonialian, Mariano (Investigaciones de Historia Económica, 2019)
Sin resumen